Cost-effective safety nets: what are the costs of reaching the poor? - Coady, David (International Food Policy Research Institute, 2003)
Which social safety-net progammes reach poor households? How cost efficient are they? This research shows that public works programmes have great potential for targeting poor households. However there is a great variability in their performance. Human capital subsidies provide a promising approach for addressing poverty and have been shown to have a substantial impact on nutrition, health, and education outcomes.